The Dearth of Democracy in South Africa: ANC’s Factionalism, State Capture Inquiry, and Riots - Takudzwa, Munhuweyi Kenneth (International Journal of Criminology and Sociology, 2022)
The 2020 Covid 19 pandemic came with good and bad news across the globe. The South African government had its most challenging moment, which found intra-party elite cohesion over state capture inquiry and corruption triggering riots in Gauteng and KwaZulu Natal. In South Africa whether they will be democratic deepening or decay will be unveiled in the article proffering for alternative solutions to resolve future conflicts in the country. Nevertheless, the article did not dispute the institutional democracy in South Africa as one of the African leading democratic state. The research used the socio-economic and political psychological analysis to unveil the July 2021 riots in South Africa. An ethnographical approach was utilized to enrich the study phenomenon, gathering data through documentary review, and multimedia platforms.